GENDER, PATRIARCHY AND DOMESTIC VIOLENCE - Gutierres de Oliveira , Marciely; Paixão, Márcia (Revista Gênero e Interdisciplinaridade, 2026)
This paper addresses a topic linked to research for the Professional Master’s Program in Public Policies and Educational Management, within the research line of Pedagogical Management and Educational Contexts (LP2) at the Federal University of Santa Maria. The theme, involving the issue of domestic violence, is one that demands a critical perspective. Today, the number of cases involving violence against women has increased significantly in various places, and even with a protective law, the rates remain high. This study uses a bibliographic approach and engages with feminist studies to understand gender issues, their relationship with patriarchy, and how domestic violence constitutes itself as a social phenomenon and a problem of health and public policy. To contextualize this study, the research references feminist authors such as Saffiotti, bell hooks, among others. This work provides a theoretical overview and also presents discussions about how domestic violence manifests itself in different spaces and in various forms, highlighting an emerging problem that remains a challenge requiring urgent attention focused on public policy investment and open dialogue from all of society.